GAMBARAN KARAKTERISTIK IBU BERSALIN DENGAN KETUBAN PECAH DINI DI RUANG PERAWATAN KEBIDANAN RSUD PURI HUSADA TEMBILAHAN TAHUN 2018 - Sasmi Agustina; Nurul Indah Sari (STIKES HUSADA GEMILANG, 2020)
Amniotic rupture early is the rupture of amniotic fluid before the time of labor can occur at the end of pregnancy or long before the time of labor. Based on health data in Riau Province, the death rate in 2013 was recorded as 135 out of 114,494 births. The cause of maternal death includes premature rupture of amniotic fluid (KPD). Based on data in the Obstetrics Treatment Room of Puri Husada Tembilahan Hospital in 2018, the incidence of maternity mothers with amniotic fluid ruptured early amounted to 260 cases out of 1,007. This study aims to find out the characteristic picture of maternity mothers with amniotic rupture early in the Obstetrics Treatment Room of Puri Husada Tembilahan Hospital in 2018. This research was conducted in the Obstetrics Treatment Room of Puri Husada Tembilahan Hospital on July 15, 2019 to July 20, 2019. This type of research is quantitative with descriptive design sampling using a total sampling of 260 people. The results of the study of most respondents were aged 20-35 years, which was 193 people (74.2%), multipara as many as 98 people (37.7%), not cephalopelvic disproportion as many as 242 people (93.1%), normal location which is as many as 232 people (89.2%). It is expected that from the results of this study Puri Husada Tembilahan Hospital, especially in the Obstetrics Treatment Room, further improves health promotion through poster media in the form of leaflets to patients experiencing pregnancy.